PENGEMBANGAN SSP FISIKA BERBASIS PENDEKATAN CTL UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS DAN MOTIVASI BELAJAR - Noor, Faiq Makhdum; Wilujeng, Insih (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2015)
This research aims to develop a learning device as Subject-Specific Pedagogy (SSP) of physics, and to improve science process skills and learning motivation of the students. This research used the 4D model. The subjects of this research were the XI grade students of Muhammadiyah High School 2 Yogyakarta. The data collecting instruments were expert validation sheets, science process skill observation sheets, questionnaire of students' response to the student books and worksheets, question-naire of students' response to teaching process, students' motivation learning sheets, and science process skill paper test. The research data were collected through observation, questionnaire, and paper test, and analyzed quantitatively. The results show as follows. (1) The development of physics SSP is carried out in accordance with the procedures of 4D model product development. (2) The results of expert's validation show the physics SSP is in the very good criteria. (3) The readability of the student books and worksheets is in the good criteria. (4) The increasing of the score of science process skills and students' learning motivation in the experimental class is higher than that in the control class. This shows that the physics SSP is fit for use in physics teaching.